EDUCATION OF SPIRITUALITY OF SENIOR STUDENTS MEANS OF FICTION (Pedagogy of Higher and Secondary Education, 2002)
Different problems and aspects o f bringing up o f spirit among young generation in studiing Ukrainian literature are opened in this article.